Optimization of decoloring conditions of crude fatty acids recovered from crude glycerol by acid-activated clay using response surface method - Su, Hong; Wang, Xue; Kim, You Geun; Kim, Sung Bae; Seo, Yang-Gon; Kim, Jin Seog; Kim, Chang-Joon (The Korean journal of chemical engineering, 2014)
Crude glycerol, a by-product of the biodiesel production process, contains a high amount of fatty acids that cannot be used directly without removing the strong dark color. This study aims to remove the color impurities in crude fatty acids, prepared by acid-precipitation and hexane extraction, using acid-activated clay as an adsorbent. The effects of bleaching temperature, contact time, the amount of acid-activated clay, and concentration of color impurities were investigated. No significant effects of bleaching temperature or contact time were observed. In an optimization study using the central composite design, complete decolorization was achieved at an optimized condition, in which 3.5 g of clay was added to 10mL of crude fatty acid solution with an optical density at 373 nm of 20. Notably, more than 80% of the peroxides was concurrently removed. However, a 37% loss in fatty acids was observed during decolorization. The clay was repeatedly used without loss of adsorption capability if it was calcined at 600 °C after use.